Recent advancements in synthesis of cyclic oligosaccharides - Endo, Hirofumi; Sun, Yu-Cong; Sasaki, Norihiko; Nokami, Toshiki (Chemical communications (Cambridge, England), 2025)
The development of synthetic methods for chemical glycosylation enables the synthesis of various oligosaccharides, including nonnatural cyclic oligosaccharides. Electrochemical glycosylation is an enabling technology not only for automated solution-phase synthesis of linear oligosaccharides but also for the chemical synthesis of cyclic oligosaccharides. In this review, recent syntheses of nonnatural cyclic oligosaccharides are also introduced, and glycosylation methodologies are focused on. The development of synthetic methods for chemical glycosylation enables the synthesis of various oligosaccharides, including nonnatural cyclic oligosaccharides.